PENGARUH CUACA TERHADAP RETURN SAHAM DI BURSA EFEK INDONESIA - Yulis Maulida Berniz; Cici Widowati (Program Studi Magister Manajemen, Universitas Pancasakti Tegal - Indonesia, 2017)
Weather factors that significantly affect stock returns on the Indonesia Stock Exchange weather hypothesis is positive and significant effect on stock returns in the Indonesia Stock Exchange. Research using daily data in the form of stock returns obtained from the data center capital markets and daily weather data obtained from the Meteorology and Geophysics Agency (BMG) in Jakarta in the form of ordinal levels. The analytical method used in this research is regression analysis linier.